Handbook of electrical power system dynamics : modeling, stability, and control - Eremia, Mircea; Shahidehpour, M., 1955- (Hoboken, New Jersey : John Wiley & Sons Inc., 2013)
This book aims to provide insights on new trends in power systems operation and control and to present, in detail, analysis methods of the power system behavior (mainly its dynamics) as well as the mathematical models for the main components of power plants and the control systems implemented in dispatch centers. Particularly, evaluation methods for rotor angle stability and voltage stability as well as control mechanism of the frequency and voltage are described. Illustrative examples and graphical representations help readers across many disciplines acquire ample knowledge on the respective.
Includes bibliographical references.
Print version record.
Keywords: Electric power system stability -- Mathematical models -- Handbooks, manuals, etc; Electric power systems -- Control -- Handbooks, manuals, etc; Electric machinery -- Dynamics -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING -- Electrical; Electric machinery -- Dynamics; Electric power system stability -- Mathematical models; Electric power systems -- Control; Handbooks and manuals; Electronic books